An inventory of concerns behind blood safety policies in five Western countries. Issue 12 (30th August 2015) - Kramer, Koen; Verweij, Marcel F.; Zaaijer, Hans L.
Abstract : BACKGROUND: The availability of costly safety measures against transfusion‐transmissible infections forces Western countries to confront difficult ethical questions. How to decide about implementing such measures? When are such decisions justified? As a preliminary to addressing these questions, we assessed which concerns shape actual donor blood safety policymaking in five Western countries. STUDY DESIGN AND METHODS: Our qualitative study involved determining which issues had been discussed in advisory committee meetings and capturing these issues in general categories. Appropriate documents were identified in collaboration with local decision‐making experts in Canada, Germany, the Netherlands, the United States, and the United Kingdom. The introduction of hepatitis B virus nucleic acid testing and selected measures against variant Creutzfeldt‐Jakob disease, West Nile virus, and Q‐fever were chosen as cases representing decision‐making on safety measures with high costs and low or uncertain added safety. RESULTS: A broad inventory of concerns was established, including: 1) nine categories of advantages and disadvantages of candidate safety policies; 2) six kinds of difficulties in assessing risks and forecasting the effects of safety policies; 3) 13 decision‐making principles; and 4) six kinds of practical barriers hampering the translation of candidate policies into decisions. CONCLUSION: Blood safety policymaking involves a wide variety of competing concerns, and approaches to reconcile these considerations are themselves contested. Developing a systematic decision‐making approach requires ethical reflection on, among others, reasonable costs of safety and the value of transparency in public policy.